Design and Development of a Palm and Coconut Stick Shaving Machine Using an Adjustable Blade - Ma'a, Mustaza; Gozali, Serano; Novison, Roni; Wijianto, Agus (UIR PRESS, 2026)
Oil palm and coconut are important crops in Indonesia that produce vegetable oil. However, both plants also generate a very large amount of waste, one of which is leaves. These leaves are often not utilized optimally and are simply wasted, even though the midrib section has the potential to be used as material for various crafts. This study aims to design and develop a stripping machine for coconut and oil palm midribs using an adjustable blade innovation, which can adapt to variations in midrib diameter to produce clean and optimal strips. The machine utilizes two blades which one adjustable blade for adapting to the midrib diameter and one fixed blade, an AC motor as the main drive, and rubber rollers as the midrib feeder. The outcome of this design is expected to help communities utilize midrib waste more effectively and contribute to increasing the added value of agricultural waste. Furthermore, the use of an adjustable blade mechanism is expected to improve the flexibility and efficiency of the stripping process.